Development for whom? Emerging donors and Africa's future. (2015) - Debrah, Isaac Ofosu; Yeboah, Thomas; Boafo, James
This paper examines the increasing partnership between emerging donors particularly China and African countries. We show that the near shift from Western development model to that of emerging donors (China) on the part of many African countries has yielded mutual benefits and at the same time demonstrating that the nature of some of these engagements portend dire consequences for Africa's future. While African nations continue to benefit through huge FDI flows, infrastructure development and diplomatic relations, China also continues to benefit through expanded access to market and exploitation of the vast mineral and energy resources to satisfy its national development goals. These forms of engagement may initially yield positive results; however, it may affect the attainment of sustained development in Africa if limited attention is paid to manufacturing. The paper concludes by suggesting some pathways for African countries to leverage this Chinese partnership in the context of post-2015 development agenda.